Income gaps: Education and inequality - Leone, Julián; Cascio, Jorge Lo (Economics and Business Review, 2020)
The aim of this paper is to analyze the employment-related real income gapsaccording to the education level reached by the working population during the 1997–2017 period. Using a panel methodology (pseudo-cohorts) it sums up that throughoutrecession, employment-related real income gaps by education level are wider, amplifyingincome inequality. During the economic boom the narrowing of the gap was dueto the weak growth in skilled employment that did not manage to recover the pre-crisisvalues. This phenomenon is typical of a labour market structure with less skilledemployment demand than its increasing supply. The employment-related differencein reduction of the real income gaps is exclusively reflected by a decline in employeesfrom the highest education segment. The whole of tertiary education although withless intensity, replicates its trend. Not only educational credentials increase future employment-related income but also starting then not completing a university degree providesa significant disparity. Gender control shows a sharp drop in its determination.